2000
DOI: 10.1021/jp002293o
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Experimental and Theoretical 17O NMR Study of Crystalline Urea:  An Example of Large Hydrogen-bonding Effects

Abstract: We report the first experimental determination of the carbonyl 17O electric-field-gradient (EFG) tensor and chemical-shift (CS) tensor of a urea-type functional group, R1NHC(O)NHR2. Analysis of magic-angle spinning (MAS) and stationary 17O NMR spectra of crystalline [17O]urea yields not only the principal components of the carbonyl 17O EFG and CS tensors, but also their relative orientations. The carbonyl 17O quadrupole coupling constant (QCC) and the asymmetry parameter (η) in crystalline urea were found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
93
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(108 citation statements)
references
References 84 publications
14
93
1
Order By: Relevance
“…18 The authors verified that the continuum method fails even at reproducing the sign of the isotropic chemical shift and that the discrete approximation is more reliable. They also verified that the rigid cluster approximation, in the case of (H 2 O) 5 provided results close to that obtained from the average over the structures from simulations. However the best agreement between the experimental and theoretical values was given by the Malkin sampling method, 13 that represented the chemical shift as a distribution of values around an average obtained from quantum calculations and not as an absolute value obtained by a single calculation.…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…18 The authors verified that the continuum method fails even at reproducing the sign of the isotropic chemical shift and that the discrete approximation is more reliable. They also verified that the rigid cluster approximation, in the case of (H 2 O) 5 provided results close to that obtained from the average over the structures from simulations. However the best agreement between the experimental and theoretical values was given by the Malkin sampling method, 13 that represented the chemical shift as a distribution of values around an average obtained from quantum calculations and not as an absolute value obtained by a single calculation.…”
Section: Introductionsupporting
confidence: 67%
“…[2][3][4][5]13,14 We used it in this work to describe the isotropic and anisotropic chemical shifts in liquid water. As a first approach, we have employed the hybrid functional B3LYP 36,37 with the purpose of studying the convergence with the number of water molecules used (cluster size).…”
Section: Quantum Mechanical Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Masunov and Dannenberg 43 investigated one-dimensional hydrogen-bonding aggregates, chains and ribbons, of urea and thiourea; these authors found the cooperative interactions for the urea and thiourea chains to be similar, whereas the cooperative interactions for both ribbons were found to be negligible. Dong et al 44 reported the first experimental determination of the carbonyl 17 O electric-field-gradient tensor and chemical-shift tensor; the strong hydrogen-bonding effects on these quantities were studied by systematically modeling the H-bond network in crystalline urea with several molecular clusters including bifurcated and other multicenter H bonds. The fundamental role of bifurcated H bonds in proteins, DNA crystal structures, and other biologically relevant systems has been amply demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Masunov and Dannenberg 29 investigated one-dimensional hydrogenbonding aggregates, chains and ribbons, of urea and thiourea; these authors found the cooperative interactions for the urea and thiourea chains to be similar, whereas the cooperative interactions for both ribbons were found to be negligible. Wu et al 30 reported the first experimental determination of the carbonyl 17 O electric-field-gradient ͑EFG͒ tensor and chemical-shift tensor; the strong hydrogen-bonding effects on these quantities were studied by systematically modeling the H-bond network in crystalline urea with several molecular clusters including bifurcated and other multicenter a͒ Author to whom correspondence should be addressed. Electronic mail: rparra1@depaul.edu H bonds.…”
Section: Introductionmentioning
confidence: 99%